델파이 분석을 통한 조경설계공모 과정의 문제점 분석 - 이주희; Joo Hee Lee; 조세환; Se Hwan Cho (한국조경학회지, 2013)
본 연구는 1983년 설계공모 제도가 한국 조경계에 도입되고 30년이 지난 현 시점에서 조경 설계공모 과정에서 발생되고 있는 문제점을 분석·고찰함으로써 향후 조경 설계공모 과정 개선에 기여할 수 있는 기초자료를 제공하기 위한 목적으로 수행하였다. 연구를 수행하기 위해 조경 설계공모에 관여하는 전문가를 대상으로 델파이 조사를 실시하여 문제점을 도출하였으며, 그 결과는 다음과 같다. 첫째, 조경설계 공모 관련 이론과 선행연구를 분석한 결과, “설계공모 방식”, “설계공모 지침”, “당선작 선정과정”, “당선작 이후 설계변화” 등 4가지 관점에서 문제점이 있는 것으로 나타났다. 둘째, 전문가 델파이 분석을 통하여 전문가들의 의견을 합의하는 과정을 이끌었고, 그 결과 총 12개의 항목으로 조경설계 공모 과정의 문제점이 도출되었는바, “설계공모 방식”에서는 “설계공모 기간의 문제”, “설계공모 방식” 등 2가지의 항목, “설계공모 지침”에서는 “비위계적이고 혼란스러운 지침”, “규정적으로 정해지는 지침”, “지침의 분량의 과다” 등 3개 항목, “당선작 선정과정”에서는 “심사위원 전문성 결여”, “비조경전문가 참여”, “심사배점 방식에 문제점” 등 3개 항목, “당선작 이후 설계변화”에서는 “발주처 설계담당자의 잦은 인사이동”, “설계기간의 기약 없는 과다연장”, “발주처의견이 과다하게 반영되는 풍토”, “원설계의 창의성을 저감시키는 발주처 의견” 등 4가지 항목이 문제점으로 나타났다. This study has been performed to analyze and consider the problems after 30 years in terms of landscape design competition process in Korea, so that it can provide the basic data, which can improve the future landscape design competition. We have used Delphi Investigation to carry out a survey that targets professionals and identifies problems. The results are summarized as follows. Firstly, the results of the analysis of Landscape Design Competition for institution theory and case studies showed that there is an issue from four perspectives which are “method of design competition”, “guidelines for design competition”, “winner selection process”, and “design changes after winning” Secondly, the process by professional Delphi performed expert analysis, and agree with expert opinion. As a result, we derived the problems of a landscape design competition system with the 12 items. Third, in the “design competition style”, two items, the “design competition style” and “problem of design public offering period” had become a problem. Fourth, the “Guidelines for design competition”, “non-hierarchical excess of the amount of instructions”, “directive determined the guidelines”, and the “provision of confusion” three items had also become a problem. Fifth, “sex expert committee review selection process winning work”, “Problems of participation”, “examination scoring system experts lack”, and “non-landscaping” had become a problem. Sixth, “The design of the original order” as much as possible “design changes after the winning work” Four “order to Comments to reduce the creativity of the design of the climate”, “original extension”, “contractor feedback of excess without the promise of frequent personnel changes”, design period of the person in charge is reflected in excess item has become a problem. I considered that a continuous research on the improvement of the problems of the landscape design competition system based on the results must be performed.